Development of wireless data transnmission using 8051 microcontroller - Zaleha, Salleh (2006)
As a human being we sometime in habit of lost an item such as keys, TV remote and so on. So we need devices that have ability searching to the lost item and save our time. By doing a research, I have found a device which meets this specification. Development board of wireless data transmission can be used to solve this matter. This board also can be used for other application such as to control the thing located in a small place which is difficult to us to enter as well as it can be used to control something located in a danger place such as ultraviolet wave. For trial, I do implement this board to locate and item. The main part of this board is microcontroller and interface with keypad and LCD display together with the requirement of radio frequency .The keypad is used to enter the names of the item and select the item. The user can then select the desired item and press the button to transmit the RF. The LCD will then will display the name of the item according to the key being pressed in keypad. Overall, this project consist of both hardware and software design. The microcontroller plays an important role to control the overall system design.